2013
DOI: 10.1007/s10856-013-4929-y
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo studies of a novel nanohydroxyapatite/superhydrophilic vertically aligned carbon nanotube nanocomposites

Abstract: An association between in vitro and in vivo studies has been demonstrated for the first time, using a novel nanohydroxyapatite/superhydrophilic vertically aligned multiwalled carbon nanotube (nHAp/VAMWCNT-O2) nanocomposites. Human osteoblast cell culture and bone defects were used to evaluate the in vitro extracellular matrix (ECM) calcification process and bone regeneration, respectively. The in vitro ECM calcification process of nHAp/VAMWCNT-O2 nanocomposites were investigated using alkaline phosphatase assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…4c). We have already observed this trend in a previous work, where [56] PDLLA/nHAp scaffolds promoted better in vitro osteogenic results and in vivo bone regeneration. However, herein we performed a deeper study involving bone formation using micro-CT and mechanical properties after scaffold implantation.…”
Section: Resultssupporting
confidence: 78%
“…4c). We have already observed this trend in a previous work, where [56] PDLLA/nHAp scaffolds promoted better in vitro osteogenic results and in vivo bone regeneration. However, herein we performed a deeper study involving bone formation using micro-CT and mechanical properties after scaffold implantation.…”
Section: Resultssupporting
confidence: 78%
“…25 CNTs, both single-walled and multiwalled types, are reported to have good osteoinductive and accelerating cell proliferative properties solely, or in combination with, nano-HA. 26 The fibroblast growth factor-incorporated CNTs have shown an increase in osteoblastic proliferation. 27 The porous chitosan scaffold, with varying degrees of nano-HA composition, has been studied by incorporating a single-walled magnetically produced CNT (B-SWCNT) and nonmagnetically produced H-SWCNT, where B-SWCNT was found to have superior biocompatibility properties.…”
mentioning
confidence: 99%
“…Several papers have been published by our group reporting the use of superhydrophilic MWCNTO-GO as is or in bioscaffolds in contact with different cell lines [39][40][41][42]. In all of these studies, we have demonstrated their non-cytotoxicity and tissue regeneration ability using animal models [43]. Recently, we demonstrated that PDLLA membranes with low MWCNTO-GO content accelerated in vivo bone regeneration and induced bone lamellar formation [43].…”
Section: Biological Assaysmentioning
confidence: 91%
“…In all of these studies, we have demonstrated their non-cytotoxicity and tissue regeneration ability using animal models [43]. Recently, we demonstrated that PDLLA membranes with low MWCNTO-GO content accelerated in vivo bone regeneration and induced bone lamellar formation [43]. Herein, we advanced this issue since we conducted in vivo studies with positive biological responses using high amounts of MWCNTO-GO in composites.…”
Section: Biological Assaysmentioning
confidence: 99%